TO INVESTIGATE THE CLINICAL CHARACTERISTICS AND RISK FACTORS OF LENS-INDUCED GLAUCOMA IN HOSPITALS - Manish Totey (Journal of Biomedical and Pharmaceutical Research, 2018)
BACKGROUND: In India's rural areas, lens-induced glaucoma (LIG) is a prevalent occurrence. Clinically, it has been known for a long time that different types of glaucoma can develop in conjunction with cataract development. Cataracts are a significant secondary glaucoma cause in the developing world. Secondary open-angle glaucoma includes phaco-lytic glaucoma and lens particle glaucoma. The iridocorneal angle is open, and lens proteins have blocked the trabecular meshwork. Secondary angle-closure glaucoma includes phacomorphic glaucoma and lens displacement glaucoma. Screening and early detection of glaucoma are crucial to begin early treatment and slow down its advancement because it frequently progresses undiagnosed until the optic nerve is irreparably injured, resulting in varied degrees of permanent visual loss.AIM: The purpose of this study was to investigate the clinical characteristics and risk factors of lens-induced glaucoma in hospitals, as well as the demographics of LIG patients.MATERIAL AND METHOD: The department of ophthalmology conducted this prospective investigation. This research was carried out in a hospital's outpatient department of ophthalmology. This was carried out repeatedly until the intended sample size of 100 instances was reached. The evaluation of the open-angle glaucoma patients involved taking a thorough medical history, which included the patient's name, age/gender, address, presenting complaints, past medical history, and systemic illnesses such as diabetes mellitus, hypertension, cardiovascular disease, asthma, use of eye or oral steroids, ocular disease, or ocular sclerosis. Informed consent was taken from the patients who satisfy the inclusion criteria.RESULTS: One hundred cases of secondary glaucoma were included in the current study. In the current study, out of 100 eyes, 31% had visual acuities between 6/60 and 6/18, and another 30% had vision between 5/60 and PL+. 18% lacked PL. Visual acuity was within the normal range in 21% of patients. In the current study, there were 18 instances of lens-induced glaucoma, of which 10 (61.1%) had phaco-morphic glaucoma, followed by 6 (27.8) cases of phaco-lytic glaucoma, one case of traumatic lens-induced glaucoma, and one case of pseudo-exfoliative glaucoma. 18% of instances of secondary glaucoma caused by steroids and 16% by lenses, respectively, were found to have lens-induced glaucoma.CONCLUSION: In order to explain the clinical profile of LIG, the current report is a cross-sectional study of 100 patients of secondary glaucoma. Pupil, developed lens, and anterior chamber depth of <1/4 CT with pseudo exfoliation The most frequent findings in the anterior segment were PACD. The most frequent findings in a fundus examination included disc hemorrhage, peripapillary atrophy, bayoneting, and bearing of circum-linear blood vessels. Superior Scotoma (SS) and Superior Arcuate Scotoma (SAS) are frequent observations in the perimetry. Grade 3 findings on gonioscopy are frequently found in patients of secondary glaucoma.KEYWORDS: Lens-induced Glaucoma, Neovascularization, Risk factors and Secondary open-angle glaucoma